PENGARUH SUBSTITUSI TEPUNG PISANG KEPOK PUTIH PADA EGGROLL TERHADAP KADAR VITAMIN C DAN DAYA TERIMA - ANGGRAINI, SINTA; , Pramudya Kurnia, STP, M.Agr; , Rusdin Rauf, STP, MP (2016)
Introduction: Kepok putih banana is a seasonal fruit which has a relatively short shelf life so it is necessary to extend the shelf life. kepok putih banana contains vitamin c that is 20,4 mg, however the utilization of kepok putih banana still limited. To increase the content of vitamin c in egg roll, it can use kepok putih banana powder substituted with wheat flour. Objective: The objective of this study is to know vitamin c content and sensory acceptance of egg roll made of kepok putih banana powder substitution. Research Method: The type of research is experimental. The research design is randomized complete block design those are three treatments and one control with two repetitions. The amount of kepok putih banana powder substitutions are 0%, 15%, 30%, and 45%. Vitamin c content is obtained by using titrimetric method and sensory acceptence is obtained by a test with 30 panelists. Statictics test by using Anova than continued by Duncan test. Result: The result from Anova showed that p value of vitamin c content is 0,114. The result from Anova showed that p value of egg roll sensory acceptence towards color 0,54, aroma 0,037, taste 0,034, texture 0,65, and totality 0,25 Conclusion: There is a difference or effect in eggroll by using kepok putih banana powder substituiton towards aroma and taste, however there is no effect on vitamin c, color, texture, and on the whole. Suggestion: Further research could also be conducted by adding kepok putih banana powder to other products, this is done for the food utilization.